A Systematic Review on the Diagnostic Accuracy of Line Probe Assay in the Rapid Diagnosis of Drug Resistant Tuberculosis in Indian Scenario - Suzana, B. Shirly; Reddy, Kishore; Bhargava, Shipra; Chauhan, Manisha (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2021)
Owing to the drastic increase in the number of patients with drug resistant TB around the world, it is important to increase the testing for it. Line probe assay (LPA) is the rapid diagnostic tool to detect drug resistant TB and it was endorsed by WHO for testing first line drugs such as Isoniazid (INH) and Rifampicin (RIF). This systematic review evaluated the accuracy of this LPA by analysing its sensitivity and specificity against the phenotypic drug susceptibility testing (DST) methods like LJ and liquid culture DST. A total of 4774 samples were included in this review from 19 articles. The average sensitivity and specificity for the detection of RIF resistance from 17 articles was 95.79% and 96.71% and for INH resistance it was 89.85% and 97.33% respectively when compared to phenotypic DST. Out of 19 articles included, 2 articles have mentioned the sensitivity and specificity for multi-drug resistant TB (MDR TB) and the average was 98.50 % and 97 % respectively. The accuracy for RIF resistance detection through first line LPA was good and the sensitivity detection for INH was less across the studies. This could be improved further in future generation assays. Our finding supports the use of LPA especially on smear positive specimens but use on smear negative specimens still be considered as studies have shown some interpretable results.